The Energy Consumption Control as Support to The Environmental and Economic Sustainability of Public Universities - Andrea Pinto Loguercio; Ruane Fernandes de Magalhães (Universitas Diponegoro, 2021)
Energy consumption at Universities follows specific standards related to the development of its education, research, and extension activities. For these activities’ continuity, the supply of energy must have a high level of reliability, without, however, compromising the economic sustainability of the institutions. That is because energy expenditures, in some cases, can be relevant for Universities, especially to public institutions in developing countries, which routinely deal with budget restrictions. On the other hand, energy efficiency and rational energy consumption, have a direct impact on these organizations' environmental sustainability indicators, such as their carbon footprint. In this sense, considering that the Universidade Federal do Rio Grande do Sul faces economic challenges, which often make investments in innovative technologies impossible, we compare strategies to optimize its energy consumption. These strategies should achieve better levels of emission reduction and economic costs related to this resource. Therefore, the objective of this study is to analyze how Public Universities, in developing countries, can optimize their energy consumption, even under budget restrictions. To this end, the results from three strategies adopted by the University, since 2016, to reduce the energy consumption are discussed: (i) increased individual monitoring of consumption points; (ii) optimization and detailed analysis of energy consumption data; and (iii) extensive implementation of reduced summer hours. With the adoption of these practices, it was observed an annual reduction in energy consumption of 6% and 20%, reaching 33.70% on average during the summer period. Thus, it was possible to guide the energy policies of the University, which can change consumption patterns, leading to a reduction in greenhouse gas emissions and a better economic equilibrium